Ralph S. Mouse - Cleary, Beverly; Zelinsky, Paul O. (New York, N.Y. : Dell, 1983)
Presents the further adventures of a motorcycle-riding mouse who goes to school and becomes the instigator of an investigation of rodents and the peacemaker for two lonely boys.
Originally published: New York : Morrow, c1982.
"A Yearling book."
"RL: 6.3, 008-012"--P. [4] of cover.
Keywords: Mice -- Fiction